Investigating the signaling properties of myeloid specific integrin αMβ2 (CD11BCD18) - Ong, Li Teng (2017)
The cell adhesion molecules integrins are important in immune homeostasis. Dysfunctional or deregulated integrins can lead to a compromised immune system or generate overt inflammatory responses. Apart from its well-established role as a phagocytic receptor, the myeloid specific integrin αMβ2 (CD11bCD18) is involved in cell migration, leukocyte survival and immune tolerance. We are therefore interested to study the signaling conduits of integrin αMβ2 and determine the roles of the integrin αMβ2 cytoplasmic tails in these events. Herein, we showed for the first time a Systemic Lupus Erythematosus associated single nucleotide polymorphism on integrin αMβ2, SNP rs1143678, exhibits pro-inflammatory properties and it generates a non-canonical docking site in integrin αM cytoplasmic tail for 14-3-3ζ. We also identified RGS10 as a possible integrin αMβ2 downstream signaling target. Finally, we generated kindlin-3 knockdown macrophages to study its regulation of integrin αMβ2 signaling in inflammation.